Dynamics of Magma Chamber Replenishment Under Buoyancy and Pressure Forces. Issue 1 (14th January 2023) - Longo, A.; Garg, D.; Papale, P.; Montagna, C. P.
Abstract: Active magma chambers are periodically replenished upon a combination of buoyancy and pressure forces driving upward motion of initially deep magma. Such periodic replenishments concur to determine the chemical evolution of shallow magmas, they are often associated to volcanic unrests, and they are nearly ubiquitously found to shortly precede a volcanic eruption. Here, we numerically simulate the dynamics of shallow magma chamber replenishment by systematically investigating the roles of buoyancy and pressure forces, from pure buoyancy to pure pressure conditions and across combinations of them. Our numerical results refer to volcanic systems that are not frequently erupting, for which magma at shallow level is isolated from the surface ("closed conduit" volcanoes). The results depict a variety of dynamic evolutions, with the pure buoyant end‐member associated with effective convection and mixing and generation of no or negative overpressure in the shallow chamber, and the pure pressure end‐member translating into effective shallow pressure increase without any dynamics of magma convection associated. Mixed conditions with variable extents of buoyancy and pressure forces illustrate dynamics initially dominated by overpressure, then, over the longer term, by buoyancy forces. Results globally suggest that many shallow magmatic systems may evolve during their lifetime under the control of buoyancy forces, likely triggered by shallow magma degassing. That naturally leads to long‐term stable dynamic conditions characterized by periodic replenishments of shallow partially degassed, heavier magma by volatile‐rich fresh deep magma, similar to those reconstructed from petrology of many shallow‐emplaced magmatic bodies. Plain Language Summary: Periodic injections of magma into shallow magma chambers are a fundamental process known to govern the evolution of magmatic systems. According to our overall understanding of magmatic systems, we simulate the time‐space dynamics in a composite magmatic system under the action of buoyancy and pressure forces. The formers are due to different chemical compositions of the shallow and deep magmas. The latter may result from chemical reactions, tectonic stress accumulation, or other deep processes. The numerical results illustrate an ample variety of situations mostly controlled by buoyancy or pressure forces. It is found that the "normal" condition for many volcanic systems is likely characterized by periodic arrivals of light batches of magma giving rise to efficient convection and mixing at shallow level, and parallel sinking of partially degassed, dense magma. This ensures essentially stable conditions unlikely to give origin to any pressure buildup leading to an eruption; it provides a mechanism for long life times of relatively small, shallow magmatic systems, and a framework for interpreting petrologic observations suggesting long sequences of mixing events at magmatic systems worldwide. Key Points: A numerical model for time‐space dynamics in shallow magma chambers replenished by deep magma is presented Evolution under pressure and buoyancy forces is initially dominated by overpressure, and over the long term by buoyant convection and mixing Lifetime evolution of volcanic systems is likely toward stable conditions with no pressure buildup leading to an eruption